State vs Market in Central and Eastern Europe - Sinziana Baltatescu; Liviu-George Maha (CES Working Papers, 2013)
Although old, the debate on whether government's intervention in economic activities can stimulate economic growth once again rose within the countries of Central and Eastern Europe. They have passed a harsh transition process, pressed on by the intention to join the EU, which involved accelerating the degree of economic freedom and fostering growth, respectively. Despite meaningful progresses, these countries have still a lot left to do in order to strengthen a solid legal system that is able to guarantee a liberal economic system, protected from political influence.
Keywords: P51; O57; 330; state; market; economic freedom; Central and Eastern Europe Romania